PENGARUH LIKUIDITAS, LEVERAGE, INTENSITAS PERSEDIAAN DAN INTENSITAS ASET TETAP PADA TINGKAT AGRESIVITAS WAJIB PAJAK BADAN - Fajar Adisamartha, Ida Bagus Putu; Noviari, Naniek (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
Results of Indonesia's tax revenues fluctuated since 2011 until 2014. This happens because not optimal taxation or the tax evasion of the taxpayer. Tax Aggressiveness is action taken to minimize the burden of the taxpayer receives tax payable. The more efficient the tax burden of State revenues from taxes will also decrease. This study was conducted to determine the effect of Liquidity, Leverage, Inventory Intensity, and Fixed Assets intensity on Aggressiveness rate taxpayer. This research was conducted taking the population of companies listed on the Stock Exchange in 2011-2014. Through purposive sampling method, researchers obtained samples of 43 companies. Data analysis technique used is multiple linear analyses. The results obtained are liquidity factor and the Inventory Intensity had positive and significant impact on the level of aggressiveness taxes. While the leverage factor, and the intensity of fixed assets had no significant effect on the level of aggressiveness of corporate taxpayers.
Keywords: Liquidity, Leverage, Inventory Intensity, Fixed Assets intensity, Aggressiveness rate taxpayer.